Exciton decay mechanism in DNA single strands: back-electron transfer and ultrafast base motions. Issue 18 (19th April 2022) - Bauer, Benjamin; Sharma, Rahul; Chergui, Majed; Oppermann, Malte
Abstract : Despite its key role in DNA photochemistry, the decay mechanism of excitons in stacked bases has remained difficult to resolve. Ultrafast polarization spectroscopy now reveals a back-electron transfer and ultrafast base motions in adenosine strands. Abstract : The photochemistry of DNA systems is characterized by the ultraviolet (UV) absorption of π-stacked nucleobases, resulting in exciton states delocalized over several bases. As their relaxation sensitively depends on local stacking conformations, disentangling the ensuing electronic and structural dynamics has remained an experimental challenge, despite their fundamental role in protecting the genome from potentially harmful UV radiation. Here we use transient absorption and transient absorption anisotropy spectroscopy with broadband femtosecond deep-UV pulses (250–360 nm) to resolve the exciton dynamics of UV-excited adenosine single strands under physiological conditions. Due to the exceptional deep-UV bandwidth and polarization sensitivity of our experimental approach, we simultaneously resolve the population dynamics, charge-transfer (CT) character and conformational changes encoded in the UV transition dipoles of the π-stacked nucleotides. Whilst UV excitation forms fully charge-separated CT excitons in less than 0.3 ps, we find that most decay back to the ground state via a back-electron transfer. Based on the anisotropy measurements, we propose that this mechanism is accompanied by a structural relaxation of the photoexcited base-stack, involving an inter-base rotation of the nucleotides. Our results finally complete the exciton relaxation mechanism for adenosine single strands and offer a direct view into the coupling of electronic and structural dynamics in aggregated photochemical systems.